The migratory transits of Peruvian transvestites/trans women towards Europe: longings, opportunities and disappointments - Pérez Ripossio, Ramiro N. (2023)
The article analyzes the migratory transits that transvestites/trans Peruvians carry out after leaving their contexts of origin. Experiencing different discriminations, vulnerabilities and violence in Peru, they decide to move to live in better conditions. For this reason, they migrate to AMBA, Argentina and after a while they move to Europe, where they go through experiences of a diverse nature. The migration of transvestites/trans Peruvians is unstable as a consequence of the hostilities they experience in receiving destinations. Consequently, they must go in search of less hostile settings, which is why mobility represents one of the main characteristics of their biographical trajectories. A qualitative methodology is used that uses the in-depth interview and, in a complementary way, the participant observation. A theoretical sample was made and the ATLAS.ti software was used to process and analyze the information through the constant comparison method. It was found that for some interviewees, migrating to the AMBA represents a springboard to Europe, since it allows them to improve their position in the social space by accessing capital. However, it was discovered that other transvestites/trans had negative experiences. In conclusion, Europe represents a chiaroscuro that articulates experiences of a different nature, linking desires, opportunities and disappointments.